Craniometric investigation and radiographic anatomy of the Red Fox (Vulpes vulpes) skull - Kanmaz, Yesım Aslan; Baygeldı, Saıme Betül; Yılmaz, Sadık (My University, 2025)
Morphometric analyses used for skull measurements are an important tool for determining sexual dimorphism and evaluating taxonomy and morphological structure. In recent years, this has led to the emergence of radiographic imaging methods that are frequently used in addition to traditional measurement techniques and allow the skull to be evaluated with the help of imaging techniques. In this study, it was aimed to measure the various dimensions of the skulls observed on radiographs and measured morphometrically and to present numerical data using the measurements. Four adult male red fox skulls were used in the study. Digital callipers were used for craniometric measurements. Morphometric measurements were based on 18 measurement points. The mean and standard deviation of craniometric measurements were determined. Radiographic images were taken ventrodorsally and laterolaterally and the necessary anatomical parts were marked on the image. The highest value of total length (TL) was 139.22±0.55 mm and the smallest value of height of foramen magnum (HFM) was 13.19±0.02 mm. As a result of the analyses, it was determined that the skulls of red foxes have some similarities with other carnivores as well as some unique anatomical features. This study can be used in different disciplines such as anatomy, morphology and osteoarchaeology in the taxonomic determination of carnivore species and thus may contribute to further studies on the red fox. In addition to morphometric measurements, radiographic imaging of the red fox for the first time is very important in terms of establishing an important data bank for breed identification.
Keywords: Vulpes vulpes; Radiography; Skull; Craniometry